Effects of Electrical Pulse Stimulation on Behaviour and Survival of Marine Benthic Invertebrates - Boute, Pim G.; Soetaert, Maarten; Reid Navarro, José A.; Lankheet, Martin J. (Frontiers in Marine Science, 2021)
Electrical pulse trawling is an alternative to conventional beam trawling for common sole (Solea solea), with the potential for higher revenues and less impact on the marine ecosystem. Concerns exist, however, that benthic invertebrates might be seriously affected by pulse fishing. Even if direct injuries and mortality were limited, changes in behaviour might compromise their survival, with potentially large impacts on food webs. Here, we investigate effects of electrical pulses on locomotion behaviour and 14-days survival of six invertebrate species from four phyla that may encounter pulse fishing gears. Electrical stimulation consisted of a Pulsed Bipolar Current at 200 V m–1, 30 Hz, 0.33 ms pulse width, and 3 s duration. We quantified species-specific behaviours before, during, and after electrical stimulation and compared these to a non-exposed control group. Responses during stimulation varied from no visible effect (echinoderms) to squirming (sea mouse) and retractions (whelk and crustaceans). Within 30 s after stimulation, all animals resumed normal behavioural patterns, without signs of lasting immobilisation. Starfish, serpent star, whelk and sea mouse showed no change in movement patterns after stimulation, whereas flying crab and hermit crab showed significant changes in activity that were indicative of increased shelter behaviour. For none of the species, survival at 14-days after stimulation was negatively affected. These findings suggest that changes in locomotion behaviour due to electrical stimulation as used in pulse trawling are unlikely to substantially compromise survival of the investigated species.